Model of Multisector And Multidimensional Approaches: An Effort to Stunting Prevention Education in Kuantan Singingi Regency, Indonesia - Yuka Martlisda Anwika; Oong Komar; Ace Suryadi; Elih Sudiapermana (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine how the multisector and multidimensional approach model is in efforts to prevent stunting in Kuantan Singingi Regency. The method used qualitative descriptive approach. The selection of informants using a purposive sample of 5 people : 1 person from the Population Control, Family Planning, Women's Empowerment and Child Protection Service (DP2KBP3A), 1 person Health Service, 1 person Health Center, 1 person the Stunting Acceleration Team (TPPS) and 1 person from the head of Posyandu. Data collection used in-depth interviews, participatory observation and documentation studies. Data analysis used qualitative analysis. The results showed that the multisector approach model was integrated from the central level, provincial level, district/city, external to village. Collaborating with the Education, Health, social, economic, agricultural, plantation sectors, etc. involving the central and regional governments, Community Institutions, community leaders and the general public. Multidimensional targets are mothers, toddlers, teenagers, prospective brides, pregnant women, children, and the elderly. The results show that stunting rates are decrease. Supporting factors are government support and an integrated stunting prevention education model with various sectors. Obstacles factors are the quality of human resources, the social culture of the local community and the stigma of stunting as negative